High-Quality Citrus: Advances in Mastication Trait Research and Applications - Guizhi Feng; Yingtian Guo; Zhenmei Cai; Chengyan Deng; Jinghua Lu (Horticulturae)
The mastication trait of citrus fruit is a key determinant of consumer preference and market value, which is influenced by a combination of genetic, environmental, and postharvest factors. This review focuses on analyzing these factors and their impacts on citrus fruit quality, with a particular emphasis on masticatory properties. The biochemical and molecular mechanisms underlying mastication traits are examined, focusing on cell wall metabolism (pectin, cellulose, lignin), cytoplasmic and intercellular matrix changes, and molecular regulation. Strategies for improving citrus quality and mastication traits are discussed, emphasizing varietal improvement through gene editing technologies, optimized cultivation practices, and advanced postharvest handling techniques. Despite significant progress, challenges remain in elucidating the complex genetic and environmental interactions governing these traits and developing sustainable management practices. Future research should integrate multiomics approaches, gene–environment interaction studies, and precision agriculture to address these challenges. This review provides a comprehensive synthesis of the current knowledge and prospective directions, aiming to guide the development of high-quality citrus varieties with enhanced mastication traits.